Atmospheric aerosols behaviour at an industrial area in Northern France. (24th September 2009) - Ledoux, F.; Courcot, D.; Courcot, L.; Aboukais, A.; Puskaric, E.
Aerosols samplings by bulk filtration and by use of a high volume cascade impactor were performed taking into account wind directions simultaneously at an urban and a rural site in Northern France. Fifteen major and trace species were considered to study characteristics of the particles collected. Evolution of the Weighted Mean Diameter vs. the wind direction, profiles of the Mass Size Function (MSF), values of the dry deposition fluxes, distribution between the coarse particles (>1 μm) and the fine particles (<1 μm), neutralisation ratio between NH4+ and SO42−, NO3− are discussed in this work.